A PROFESSION OF ACCOUNTING-OR OF ACCOUNTANCY? - Bower, James B. (The Accounting Review, 1957)
The article discusses the differences between the profession of accounting and the profession of accountancy. It lists the definitions of the terms which brings one to the conclusion that there is no profession of accountancy but there is a profession of accounting, namely public accounting. The article suggests that a profession should exist if practitioners are to receive full professional recognition and status. It defines the profession of accounting, a controller's obligation to judge, measure and disclose which extends through the internal and external fibre of the organization. It discusses the question of whether a controller can obtain true professional status and enumerates the four specific requisites against which the professional status of a controller can be measured, which are, special training for a degree distinct from the usual degrees in Arts and Science, principally mental rather than manual or artistic skill, recognizing the duty of public service and the compliance to a code of ethics for controllership.